Case Report: A Case Series Using Natural Anatomical Gaps—Posterior Cervical Approach to Skull Base and Upper Craniocervical Meningiomas Without Bone Removal - Lilla, Nadine; Kessler, Almuth F.; Weiland, Judith; Ernestus, Ralf-Ingo; Westermaier, Thomas (Frontiers in Surgery, 2021)
Background: Anteriorly located tumors of the upper cervical spine and craniovertebral junction (CVJ) are a particular surgical challenge. Extensive approaches are associated with pain, restricted mobility of neck and head and, for case of foramen magnum and clivus tumors, with retraction of brainstem and cerebellum. Methods: Four symptomatic patients underwent resection of upper cervical and lower clivus meningiomas anteriorly located to the CVJ without laminotomy or craniotomy using a minimally invasive posterior approach. Distances of natural gaps between C0/C1, C1/C2 as well as C2/C3 were measured using preoperative CT scans and intraoperative lateral x-rays. Results: In all patients, safe and complete resection was conducted by opening the dura between C0/C1, C1/C2 and C2/C3. There were no surgical complications. Local pain was very low in all patients and postoperative recovery extremely fast. All tumors had a rather soft consistence allowing mass reduction prior to removal of the tumor capsule and were well separable from lower cranial nerves and vascular structures. Conclusion: If tumor consistence is appropriate for a careful mass reduction before removal of the tumor capsule and if tumor margins are not firmly attached to crucial structures, upper cervical, foramen magnum and lower clivus meningiomas can be safely and completely removed through natural gaps in the CVJ. Both prerequisites become clear early during surgical procedure. Thus, this tumor entity may be planned using this minimally invasive approach and extended if tumor consistence turns out to be less soft or if crucial structures cannot be easily separated from the tumor.